Food availability and predation risk, rather than intrinsic attributes, are the main factors shaping the reproductive decisions of a long‐lived predator. (3rd May 2016) - Hoy, Sarah R.; Millon, Alexandre; Petty, Steve J.; Whitfield, D. Philip; Lambin, Xavier
Summary: Deciphering the causes of variation in reproductive success is a fundamental issue in ecology, as the number of offspring produced is an important driver of individual fitness and population dynamics. Little is known, however, about how different factors interact to drive variation in reproduction, such as whether an individual's response to extrinsic conditions (e.g. food availability or predation) varies according to its intrinsic attributes (e.g. age, previous allocation of resources towards reproduction). We used 29 years of reproductive data from marked female tawny owls and natural variation in food availability (field vole) and predator abundance (northern goshawk) to quantify the extent to which extrinsic and intrinsic factors interact to influence owl reproductive traits (breeding propensity, clutch size and nest abandonment). Extrinsic and intrinsic factors appeared to interact to affect breeding propensity (which accounted for 83% of the variation in owl reproductive success). Breeding propensity increased with vole density, although increasing goshawk abundance reduced the strength of this relationship. Owls became slightly more likely to breed as they aged, although this was only apparent for individuals who had fledged chicks the year before. Owls laid larger clutches when food was more abundant. When owls were breeding in territories less exposed to goshawk predation, 99·5% of all breeding attempts reached the fledging stage. In contrast, the probability of breeding attempts reaching the fledging stage in territories more exposed to goshawk predation depended on the amount of resources an owl had already allocated towards reproduction (averaging 87·7% for owls with clutches of 1–2 eggs compared to 97·5% for owls with clutches of 4–6 eggs). Overall, our results suggested that changes in extrinsic conditions (predominantly food availability, but also predator abundance) had the greatest influence on owl reproduction. In response to deteriorating extrinsic conditions (fewer voles and more goshawks), owls appeared to breed more frequently, but allocated fewer resources per breeding attempt. However, intrinsic attributes also appeared to have a relatively small influence on how an individual responded to variation in extrinsic conditions, which indicates that owl reproductive decisions were shaped by a complex series of extrinsic and intrinsic trade‐offs. Abstract : Many studies have examined the effect of food availability and predation risk on breeding decisions in isolation. In this study however we took a comprehensive approach and examined how both food availability, predation risk and attributes intrinsic to individuals interacted to shape reproductive decisions. We also provide some empirical evidence to suggest that long‐lived predators alter their life‐history strategies in response to changes in multiple interacting environmental factors.